Developing Additional Features into Ilias Learning Management System - Hasan, Payman; Varol, Asaf (Niyazi ÖZDEMİR, 2017)
>Electronic learning (e-learning) has changed learning and teaching design round the world, it have been advanced by educational institutes with large efforts. Learning Management System (LMS)   is one of the significant web based invention to e-learning platform. One of the LMS is ILIAS, which is a web based LMS, advanced by using best open source technology PHP, MySQL and Apache is used as web server. ILIAS is sophisticated in German but it also supports multiple languages including English. The aim of the research is to learn more about ILIAS, examine ILIAS to search for missing feature in ILIAS. Thus, the goals of the study will be writing codes to add three missing features to ILIAS. Those features are: Date filter for e-mails, Move E-mails to Folders by Drag and Drop and Text formatting editor for message content.
Keywords: Engineering; Mühendislik